INNOVATIVE IMPROVEMENTS TO THE CHX-3M2 INDUSTRIAL DIRT CLEANING BRUSH (Journal of Science-Innovative Research in Uzbekistan, 2024)
The equipment used for cleaning in the initial processing of seeded cotton plays a crucial role in cotton ginning operations. Typically, this machinery is installed in the cleaning sections of cotton ginning enterprises, where it ensures the effective removal of dirt and other impurities from the raw cotton. However, the specific location and arrangement of this equipment can vary depending on the layout and design of each facility. These variations in equipment placement aim to optimize efficiency in the cleaning process and ensure seamless integration into the overall cotton processing workflow